2021
DOI: 10.1002/jso.26644
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of high‐grade nonfunctional pancreatic neuroendocrine carcinoma is associated with improved survival

Abstract: Background and objectives: The role of surgery in the treatment of nonfunctional pancreatic neuroendocrine carcinomas (PNEC) is not well defined. This study investigated the effect of surgical resection on cause-specific survival compared with nonoperative management.Methods: The Surveillance, Epidemiology, and End Results Program (SEER) database was utilized to identify patients with nonfunctional pancreatic neuroendocrine carcinoma diagnosed between January 1, 2004 and December 31, 2015. Survival was modeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Subsequently, 2 retrospective analyses also supported the notion that palliative-intent resection of the primary tumor and/or radiation therapy may significantly improve survival for metastatic pNEC. In a retrospective analysis of patients with nonfunctioning pancreatic NECs of all stages, Jiang et al 29 observed that, in the metastatic setting, only surgical resection of the primary tumor (hazard ratio [HR], 0.18; P < 0.01) or chemotherapy improved survival outcomes for patients (HR, 0.56; P < 0.01). Furthermore, cause-specific survival after primary tumor resection was 15 months (interquartile range, 8–50) versus 5 months (interquartile range, 1–13; P < 0.01), regardless of whether patients received chemotherapy 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, 2 retrospective analyses also supported the notion that palliative-intent resection of the primary tumor and/or radiation therapy may significantly improve survival for metastatic pNEC. In a retrospective analysis of patients with nonfunctioning pancreatic NECs of all stages, Jiang et al 29 observed that, in the metastatic setting, only surgical resection of the primary tumor (hazard ratio [HR], 0.18; P < 0.01) or chemotherapy improved survival outcomes for patients (HR, 0.56; P < 0.01). Furthermore, cause-specific survival after primary tumor resection was 15 months (interquartile range, 8–50) versus 5 months (interquartile range, 1–13; P < 0.01), regardless of whether patients received chemotherapy 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of patients with nonfunctioning pancreatic NECs of all stages, Jiang et al 29 observed that, in the metastatic setting, only surgical resection of the primary tumor (hazard ratio [HR], 0.18; P < 0.01) or chemotherapy improved survival outcomes for patients (HR, 0.56; P < 0.01). Furthermore, cause-specific survival after primary tumor resection was 15 months (interquartile range, 8–50) versus 5 months (interquartile range, 1–13; P < 0.01), regardless of whether patients received chemotherapy 29 . Feng et al 30 noted that the 50 of 350 patients (14.3%) who underwent resection of their pancreatic primary with or without metastasectomy and chemotherapy had significantly improved median overall survival compared with those who did not undergo surgery (12 vs 8 months, respectively; HR, 0.338 [95% confidence interval, 0.269–0.560]; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Other literature argued that neuroendocrine tumors have been regarded as one of few tumor types in which debulking operation could still yield survival benefits in metastatic disease ( 22 , 23 ). Several previous studies have demonstrated the feasibility and safety of cancer-directed surgery in metastatic PanNET patients ( 24 , 25 ). However, these publications only included small sample sizes of patients or analyzed patients with various metastatic sites.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a subset of patients presenting with local or locoregional disease may benefit from surgical excision with curative intent. 11,12 In these cases, it is essential that occult disease is ruled out with fluorodeoxyglucose positron emission tomography/ computed tomography (FDG PET/CT) staging and multidisciplinary discussion is also required. 13 Many patients will experience recurrence following surgery, with a retrospective analysis of data from 119 patients with pancreatic (Panc)-NECs reporting a median time to recurrence or metastasis of 7 months.…”
Section: Resectable Cases: Surgery With or Without Chemotherapymentioning
confidence: 99%